AUKUS and the role of ASEAN centrality in managing regional security affairs - Prayitno, Heru (Technium Social Sciences Journal, 2021)
Australia, the United Kingdom, and the United States of America announced the formation of the AUKUS pact covering the Indo-Pacific region. Many countries gave different reactions to the formation of the pact, which, among others, aimed at developing cooperation in nuclear-powered defense among the parties involved. Many observers also viewed that AUKUS is aggressively meant to suppress China in the Asia-Pacific by equipping Australia, its ally in the region, with nuclear-powered submarines. ASEAN countries gave different views on the issue of AUKUS that suggest the division of ASEAN’s interests over the issue. Some experts even view that the AUKUS issue is increasingly weakening ASEAN, which struggles to maintain its unity and "centrality" in regional security affairs. This paper argues that ASEAN, with its unity and centrality, remains the primary guardian of regional peace and security and will forever remain at the "driving seat" of regional security management, which major countries cannot ignore. This paper will review the importance of ASEAN in maintaining peace, security, and stability in the region. The preservation of regional peace and security will ultimately provide prosperity for the people and countries of the Southeast Asian region, as stated in the Bangkok Declaration, which underlies the formation of ASEAN. This paper will also examine how ASEAN deals with current challenges as well as major powers in the region before analyzing the effectiveness of ASEAN centrality in managing regional security affairs.